LRP8, modulated by miR-1262, promotes tumour progression and forecasts the prognosis of patients in breast cancer. (4th May 2022) - Li, Ling; Qu, Wen-Hui; Ma, Hui-Ping; Wang, Li-Li; Zhang, Yan-Bo; Ma, Yuan
Abstract: This research was designed to detect the function of low-density lipoprotein receptor (LDLR)-related protein 8 (LRP8) in breast cancer (BC). Our results revealed that LRP8 was highly expressed in BC tissues and cell lines compared with human normal breast tissues. The poor prognosis of patients with BC was associated with the up-regulation of LRP8 while inversely connected with overexpression of miR-1262. Functionally, LRP8 depletion in BC cells impaired the proliferative, clonogenic, invasive, and migratory capabilities, which was consistent with the effects of upregulated miR-1262. Bioinformatics prediction and luciferase reporter assay confirmed that miR-1262 was an upstream factor for LRP8 and negatively regulated the expression of LRP8. Further experiments illustrated that the co-transfection of miR-1262 antamir and si-LRP8 could significantly suppress the promoting impacts caused by the transfection of miR-1262 antamir alone. These findings highlighted that LRP8 accelerated the BC development by contributing cellular aggressiveness, which was modulated by miR-1262.